When language shapes perception - Plebe, Alessio; De La Cruz, Vivian M. (Rivista Italiana di Filosofia del Linguaggio, 2015)
The idea that language molds our thinking has met with varying degrees of favor in the history of philosophy and linguistics. A rather puzzling aspect of this debate is the lack of rigorous demonstration or rebuttal of the language-thought connection. We believe that one obstacle is the intrinsic difficulty in treating “thought” as a measurable dependent variable in empirical, replicable, experiments. We plead the case for a more humble, but more verifiable, aspect of linguistic relativity: by looking at cases where language shapes our perception, instead of “thought” generally. We target the domain of color terms, a field where the effects of language in shaping perception have been more striking, even if the details are highly debated, and also discuss a different kind of perception, one related to emotion terms. We argue that in this case, there is also a continuum in the proprioceptive determinants of emotions, which is structured into discrete categories by language.